The interactivity and independence of Recovery challenges and coping strategies for ICU survivors and their caregivers: a systematic review and Meta-synthesis - Zeyi Zhang; Longshan Yang; Heng Cao (BMC Nursing)
Abstract Background The post-ICU home recovery period requires patients and caregivers to confront recovery challenges and adopt coping strategies as a family dyad, necessitating effective dyadic interaction patterns. Existing qualitative research shows that the dyads face interactive or independent challenges and employs varying coping strategies, which may include strong communication or, conversely, avoidance. However, a single qualitative study alone might offer limited generalizability, and there is a lack of broader, more nuanced understanding about the recovery challenge and copings among ICU survivors and caregivers. This meta-synthesis aims to figure out the interactivity and independence of challenges and coping strategies during the recovery process for ICU survivors and caregivers. Methods This is a meta-synthesis of qualitative studies, which was guided by the Stress and Coping Framework. We systematically reviewed six electronic databases, including PubMed, Medline, the Cochrane Library, CINAHL, PsycArticles, and PsycInfo, for relevant qualitative studies published from inception to January, 2024. We utilized a content analysis approach for data analysis. Presentation of this synthesis adhered to the PRISMA guideline and the ENTREQ guideline. Results After full-text screening, 49 studies were included. Four themes with 16 sub-themes emerged from this synthesis including, interactivity of recovery challenges for ICU survivors and caregivers (subthemes: Life was turned upside down, Situational overstrain, Isolation without compassion, Empowerment conflicts, Marginalized support), independence of recovery challenges for ICU survivors and caregivers (subthemes: Recovery means silent suffering, Gap in memory, Sacrificing to caregiving), interactivity of recovery coping strategies for ICU survivors and caregivers (subthemes: Reorientation of mindset, Cultivating inner power, Sharing burden with an open-ear, Going through thick and thin together, Negotiating care level), and independence of recovery coping strategies for ICU survivors and caregivers (subthemes: Wearing a faked smile, Developing daily routine, Seeking respite). Conclusions The findings suggest that ICU survivors and caregivers experience overlapping yet distinct challenges during recovery, often involving shared coping strategies, alongside a need for individual space. These results support the presence of both interactivity and independence in recovery challenges and coping strategies for ICU survivors and their caregivers. Therefore, we call for future dyadic or family interventions to target both ICU survivors and caregivers, taking advantage of their interactivity and desire for gradual independence, so that fostered individualized coping strategies adapted to flexible contexts.